A real-time MRI investigation of the role of lingual and pharyngeal articulation in the production of the nasal vowel system of French. (May 2015) - Carignan, Christopher; Shosted, Ryan K.; Fu, Maojing; Liang, Zhi-Pei; Sutton, Bradley P.
Abstract: It is well known that, for nasal vowels, traditional estimation of the shape of the vocal tract via inference from acoustic characteristics is complicated by the acoustic effects of velopharyngeal coupling (i.e. nasalization). Given this complexity, measuring the shape of the vocal tract directly is, perhaps, a more desirable method of assessing oro-pharyngeal configuration. Real-time MRI (rt-MRI) allows us to explore the shape of the entire vocal tract during the production of nasal vowels. This permits us to better assess the contribution of the oro-pharyngeal acoustic transfer function to the acoustic signal, which is otherwise obscured by the conflation of the independent oro-pharyngeal and nasal acoustic transfer functions. The oro-pharyngeal shape associated with nasal vowels has implications for both synchronic and diachronic phonology, particularly in French, where descriptions of nasal vowels have long suggested that differences in oral articulation, in addition to velopharyngeal coupling, serve to distinguish oral and nasal vowels. In this study, we use single-slice rt-MRI (midsagittal slice) and multi-slice rt-MRI (oral, velopharyngeal, mediopharyngeal, and lower pharyngeal slices) to examine three nasal vowels / ɛ ˜, ɑ ˜, ɔ ˜ / and their traditional oral counterparts /ɛ, a, o/ as produced by three female speakers of Northern Metropolitan French (NMF). We find evidence of lingual and pharyngeal articulatory configurations which may, in some cases, enhance formant-frequency-related acoustic effects associated with nasalization, viz., modulation of F1 and F2. Given these findings, we speculate that the synchronic oral articulation of NMF nasal vowels may have arisen—at least in part—due to misperception of the articulatory source of changes in F1 and F2, rather than to mere chance, as has been argued. Abstract : Highlights: We analyze rt-MRI data from oral/nasal vowels produced by three French speakers. Measures include vocal tract area estimates and PC analyses of pixel intensities. Some oral articulations of the nasal vowels enhance nasalization's acoustic effects. Evidence of enhancement observed for both lingual and pharyngeal articulation. Synchronic articulation likely resulted from diachronic change due to misperception.